Seeker of knowledge : the man who deciphered Egyptian hieroglyphs - Rumford, James, 1948- (Houghton Mifflin, 2000)
A biography of the French scholar whose decipherment of the Egyptian hieroglyphic language made the study of ancient Egypt possible.